Model Vector Autoregressive Exogenous dan Aplikasinya pada Curah Hujan Kota Makassar - Sukarna; Wahidah Sanusi; Serly Diliyanti Restu Ningsih (Jurusan Matematika FMIPA UNM, 2019)
This type of research is applied research that aims to predict rainfall in Makassar city VARX model using. The model was developed from the VARX model VAR by adding exogenous factors that influence the precipitation like Sea Surface Temperature (SST) Nino 3.4, the Southern Oscillation Index (SOI), and Dipole Mode Index (DMI). Rainfall data used in this researrchis the monthly rainfall data in Makassar city from 1987-2016 year on three stations, namely Panaikang, Paotere, and Biring Romang as endogenous factors. This data is retrieved from the Great Hall the Meteorology, Climatology, and Geophysics Region IV Makassar. VARX model formation through several stages, namely : test stasioneritas, the determination of the optimal lag length, test causality, diagnostic models, the establishment of the model of forecasting and VARX. The result showed that the average peak rainfall in Makassar city occurred in March and then come down exponentially. In May the chance of occurrence of very little rain.The model obtained in this study deserves to be used to predict rainfall in the next period.Keywords: , , ,